Analisis Unsur Intrinsik Cerpen Digital pada Laman Kompasiana.com Edisi Cerpen Pendidikan dan Potensinya Sebagai Bahan Ajar di SMA - Setyawati, Icmi Nur Risma; Suntoko, Suntoko; Nurhasanah, Een (Riwayat: Educational Journal of History and Humanities, 2025)
This study analyzes the intrinsic elements found within five short stories published on Kompasiana: Berteman Karena Harus, Kumbang yang Merindukan Rembulan, Hari Bersama Guru di Embung Hutan Cantik, Mengejar Pelangi Senja, and Mobil Tua Bapak. The elements examined include theme, characters and characterization, plot, setting, point of view, language style, and moral message. The results show that each short story carries a distinct theme friendship, reflection, education, perseverance, and sincerity with main characters depicted in depth and supporting characters that enhance conflict and narrative dynamics. All stories employ progressive (chronological) plots, with settings of place, time, and social context that support the development of the storyline. The use of both first- and third-person points of view creates either intimacy or narrative breadth. Various language styles (emphasis, comparison, irony, repetition) enrich the stories expression and meaning. Each short story contains an important message, such as the value of honest communication, self-acceptance, cooperation, perseverance, and family and sincerity. Overall, the analysis demonstrates that the intrinsic elements in this short story anthology work harmoniously to convey moral values and develop character. Furthermore, this study can be used as a reference for literary learning and as a teaching material to support the development of literature in the future.